3 - L’agir symbolique du public sur la scène musicale congolaise - Tsambu Bulu, Léon (Africa Development, 2021)
There is a spatial and social dichotomy between artists and their audience. The stage is conceived as a mystical, sacred ecumene, a citadel separated from the public by a neutral zone. Considering the musical stage as one of the founding loci of the invisible public space, this study aims to understand and explain the general practices taking place in Congolese concerts, and in particular the behaviour of the audience that, far from playing the passive role of simple listeners/ applauders, is in turn a producer of symbolic performances. Thus, during concerts, the audience may have access to the stage ecumene, either to congratulate the star or artists, or to participate in the performance, or on its own quest for symbolic power and social recognition. From this standpoint, this study demonstrates that, far from being an ivory tower, the Congolese musical podium remains a relatively convivial and inclusive locus, extending hospitality to the audience to the point of reducing the unequal power relationship (between the dominant and the dominated) underlying the modern stage. But beyond these strategic behaviours on the part of the artists and the audience, the study also discusses the violence that also occurs on the stage.